Adaima settlement burials : giving the burials context - Bohac, Jeri L. (My University, 2013)
The purpose of studying the Predynastic site of Adaima is to place the nine burials found in the settlement area within their archaeological context using AutoCAD and plan maps, determine the importance of the individuals buried (both human and animal) through iconography, grave goods, and settlement comparisons, and to determine why the burials occurred in the settlement rather than the cemeteries by comparison. The dog burials appear to be placed away from the living areas while infant burials are closer. Additionally, dogs were depicted in hunting scenes on ceramics and rock carvings as part of an elite practice to control chaos. With little difference between the cemeteries and settlement burials, it may have been the family's choice where to bury their child or an issue of cost.
Keywords: Egypt--History--To 332 B.C.--Congresses.; Egypt--Antiquities--Congresses.; Excavations (Archaeology)--Egypt--Congresses.